A regulated synthetic operon facilitates stable overexpression of multigene terpenoid pathway in Bacillus subtilis. (1st February 2020) - Abdallah, Ingy I; Xue, Dan; Pramastya, Hegar; van Merkerk, Ronald; Setroikromo, Rita; Quax, Wim J
Abstract: The creation of microbial cell factories for sustainable production of natural products is important for medical and industrial applications. This requires stable expression of biosynthetic pathways in a host organism with favorable fermentation properties such as Bacillus subtilis . The aim of this study is to construct B. subtilis strains that produce valuable terpenoid compounds by overexpressing the innate methylerythritol phosphate (MEP) pathway. A synthetic operon allowing the concerted and regulated expression of multiple genes was developed. Up to 8 genes have been combined in this operon and a stably inherited plasmid-based vector was constructed resulting in a high production of C30 carotenoids. For this, two vectors were examined, one with rolling circle replication and another with theta replication. Theta-replication constructs were clearly superior in structural and segregational stability compared to rolling circle constructs. A strain overexpressing all eight genes of the MEP pathway on a theta-replicating plasmid clearly produced the highest level of carotenoids. The level of transcription for each gene in the operon was similar as RT-qPCR analysis indicated. Hence, that corresponding strain can be used as a stable cell factory for production of terpenoids. This is the first report of merging and stably expressing this large-size operon (eight genes) from a plasmid-based system in B. subtilis enabling high C30 carotenoid production.